Efficacy of Nonthermal Atmospheric Pressure Plasma for Tooth Bleaching - Seoul Hee Nam; Hae June Lee; Jin Woo Hong; Gyoo Cheon Kim (The Scientific World Journal)
The conventional light source used for tooth bleaching has the potential to cause thermal damage, and the actual role of the light source is doubtful. In this study, we evaluated bleaching efficacy, temperature, and morphological safety after tooth bleaching with nonthermal atmospheric pressure plasma. Tooth bleaching combined with plasma had improved efficacy in providing a higher level of brightness. The temperature of the pulp chamber was maintained around 37°C, indicating that the plasma does not cause any thermal damage. The morphological results of tooth bleaching with plasma did not affect mineral composition under scanning electron microscopy (SEM) observations. On the basis of these results, the application of plasma and low concentration of 15% carbamide peroxide (CP) has a high capability for effective tooth bleaching. It can be documented that plasma is a safe energe source, which has no deleterious effects on the tooth surface.